Musikalisasi Dakwah di Kalangan Gen Z (Studi Kasus K.H. Muhammad Ali Shodiqin) - Muhammad, Faik; Luhur, Firdaus; Sahrul, Dede; Iqbal, Muhammad; Sahrul, Sahrul (Journal of Communication Studies, 2024)
Da'wah is an activity that aims to awaken humans to obey Islamic law and obtain happiness in this world and the afterlife. According to Amuni Syakir, da'wah has two main meanings: development and coaching. Da'wah is an activity that aims to persuade or advise other people to do good things in accordance with Islamic teachings and abstain from bad deeds. This da'wah is intended for individuals and the social life of society. In this modern era, da'wah is not only limited to delivering it in one event such as a recitation but can also be done through various other media, including social media. Preachers have various ways to spread knowledge. With advances in civilization and technology, da'wah methods have also become more diverse. In line with this, music emerged as a medium for preaching. Music is a combination of sound art and instruments used to express various things. By including elements of da'wah art, it is not only aimed at believers but can also reach all groups. Music is often associated with entertainment which is a human need. In seeking pleasure, humans can use various methods as long as they do not deviate from Islamic teachings. Humans naturally tend to like pleasant things and avoid scary things. Therefore, preachers should start their preaching by giving interesting and encouraging hopes before conveying threats. A preacher should first give targhib (good news) before tarhib (threats). The calming method as applied by the Prophet in preaching is to make it easier and not difficult and lighten and not burdensome. Many texts in the Qur'an and Sunnah texts show that Allah prefers ease to difficulty.